Resiliensi Mantan Narapidana Narkoba untuk Membangun Kembali Personal Branding melalui Penyuluhan: (Studi pada Yayasan BARAMATA/ Barisan Para Mantan Narapidana dan Tahanan di Lengkongsari, Kecamatan Tawang, Tasikmalaya) - Mukaromatun, Aprilia; Herwina, Wiwin; Novitasari, Nastiti (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Drug abuse has legal and social impacts, especially with the negative stigma of society still attached, so former drug convicts need resilience. Where resilience increases from adversity to continue a more quality life. The purpose of this study was to find out how resilient former drug convicts are to rebuild personal branding through counseling. The method used is qualitative method. Data collection techniques use purposive sampling and data collection techniques from interviews, observations and documentation. This study resulted in the resilience process of former drug convicts both with indicators of self-esteem, social support, spiritual, and positive emotions. However, efforts to rebuild personal branding through counseling are not carried out consistently, planning has not been optimal and only relies on media publications, there is no evaluation and development of counseling. Even so, the community and counseling participants still appreciate former drug convicts who conduct counseling even though the personal branding built is not entirely successful. The conclusion in this study is that the resilience of former drug convicts to rebuild personal branding through counseling results in changes by experiencing increased self-esteem, better social, spiritual support, and increased positive emotions even though personal branding has not been maximized. Keywords: resilience, personal branding, counseling, inmates